Evaluation Of The Textbook "My Best Reading" Based On The Instrument By Mike Horsley And Kevin Laws - Abdul Syahid; Iffa Kharimah; Umi Maisarah; Meisya Rawenda; Kholida Ziya (Jurnal Ilmu Pendidikan Nasional (JIPNAS), 2024)
This study discusses the importance of textbook evaluation in education to ensure the quality and effectiveness of the learning process. Textbooks not only present information but also assist teachers in designing the curriculum, crafting learning activities, and assessing student progress. Therefore, a comprehensive evaluation of textbooks is crucial to assess their suitability for educational needs. This research adopts a descriptive qualitative approach and utilizes the evaluation instrument developed by Mike Horsley and Kevin Laws to evaluate the "My Best Reading" textbook. The evaluation results provide valuable insights into the strengths and weaknesses of the textbook and its contribution to improving the quality of educational materials. However, the study has limitations that need to be considered in designing more comprehensive recommendations for enhancing instructional materials.